2008
DOI: 10.1017/s0007114508079610
|View full text |Cite
|
Sign up to set email alerts
|

Effect of coffee and tea on the glycaemic index of foods: no effect on mean but reduced variability

Abstract: Coffee and tea may influence glycaemic responses but it is not clear whether they affect the glycaemic index (GI) value of foods. Therefore, to see if coffee and tea affected the mean and SEM of GI values, the GI of fruit leather (FL) and cheese puffs (CP) were determined twice in ten subjects using the FAO/WHO protocol with white bread as the reference food. In one series subjects chose to drink 250 ml of either coffee or tea with all test meals, while in the other series they drank 250 ml water. The tests fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…Studies examining the effect of coffee on glucose metabolism have reported controversial results. Whereas some studies, like ours, found similar glucose and insulin responses 2-3 h after consumption of either regular coffee or water (33)(34)(35)(36)(37)(38)(39) , others showed increased 2-h glucose and insulin AUC for regular coffee compared with either water (40) or decaffeinated coffee (13,40,41) . Moreover, two studies reported a lower glucose AUC for decaffeinated coffee compared with regular coffee (42) or water (43) .…”
Section: Discussionmentioning
confidence: 40%
“…Studies examining the effect of coffee on glucose metabolism have reported controversial results. Whereas some studies, like ours, found similar glucose and insulin responses 2-3 h after consumption of either regular coffee or water (33)(34)(35)(36)(37)(38)(39) , others showed increased 2-h glucose and insulin AUC for regular coffee compared with either water (40) or decaffeinated coffee (13,40,41) . Moreover, two studies reported a lower glucose AUC for decaffeinated coffee compared with regular coffee (42) or water (43) .…”
Section: Discussionmentioning
confidence: 40%
“…However, we do not believe this to be a problem because, compared with drinking water, coffee and tea have no significant effect on AUC (Young and Wolever, 1998) or GI (Aldughpassi and Wolever, 2009) and may actually reduce variation in GI (Aldughpassi and Wolever, 2009). …”
Section: Effect Of Subject Characteristics On Gimentioning
confidence: 81%
“…Furthermore, factors known to create bias or increase random error in the results of GI testing are not among the criteria used to judge the quality of clinical trials, namely: the number of subjects, 28 blood sampling schedule, 29 the precision of the glucose analytical method, 4 , 30 the precision of the measure of fasting glucose, 4 , 31 the number of reference food tests, 4 , 32 within subject variation of AUC elicited by the reference food, 4 subject preparation, 4 , 33 the amount of available carbohydrate fed to subjects, 28 food composition 34 and the nature of the drink consumed with the test meals. 4 , 35 Our GI methodological quality assessment did not include an assessment of randomization. As GI testing involves multiple treatments taken by each subject over a period of time, formal randomization of the order of treatments may not be desirable or ideal.…”
Section: Discussionmentioning
confidence: 99%